2009
DOI: 10.1259/dmfr/63019695
|View full text |Cite
|
Sign up to set email alerts
|

Periapical radiography and cone beam computed tomography for assessment of the periapical bone defect 1 week and 12 months after root-end resection

Abstract: On average, the periapical bone defect measured on periapical radiographs was approximately 10% smaller than on coronally sectioned CBCT images 1 week post-operatively. More remaining defects were detected 1 year after periapical surgery on CBCT images than on periapical radiographs, but it is uncertain how this information is related to success or failure after root-end resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 20 publications
5
62
0
2
Order By: Relevance
“…The detection rate of periapical lesions in the coronal plane was 67%, and only 5% of the lesions were diagnosed with periapical radiographs. In conclusion, Christiansen et al (20) reported that that more periapical lesions are diagnosed using CBCT than using periapical radiography.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The detection rate of periapical lesions in the coronal plane was 67%, and only 5% of the lesions were diagnosed with periapical radiographs. In conclusion, Christiansen et al (20) reported that that more periapical lesions are diagnosed using CBCT than using periapical radiography.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, 2 additional variables, expansion of the cortical bone and destruction of the cortical bone, were added to the 6-point (0-5) scoring system ( Figure 1). It has also been reported that this new scoring system provides more reliable data for the detection of periapical lesions (13,19,20).…”
mentioning
confidence: 84%
“…Uma avaliação de defeitos ósseos periapicais após apicectomias, comparando a radiografia periapical e TCFC, demonstrou que o defeito ósseo periapical medido em radiografias periapicais foi aproximadamente 10% menor que nas imagens da TCCB. Além disso, mais defeitos restantes foram detectados na TCFC do que na radiografia 24 . Nas mensurações desta pesquisa, algumas medidas tiveram valores numéricos superiores na TCFC do que na radiografia, pela melhor visualização das bordas da FLP e ao acesso à região crítica na TCFC, também dificultado dependendo das angulações horizontal e vertical dos exames radiográficos.…”
Section: Resultados Discussãounclassified
“…Christiansen ve ark. 16 periapikal kemik yıkılımın tedavi sonrası iyileşmesini geleneksel periapikal radyografi ve CBCT kullanarak değerlendirmişlerdir. Buna göre yapılan tedaviden 1 yıl sonraki kontrolde periapikal radyografilerle iyileşme görülürken CBCT ile hala tam iyileşme görülmemektedir.…”
Section: Apikal Periodontitisin Tespitiunclassified